2018
DOI: 10.3390/tropicalmed3020045
|View full text |Cite
|
Sign up to set email alerts
|

First Aid and Pre-Hospital Management of Venomous Snakebites

Abstract: Background: Antivenom is the definitive treatment for venomous snakebites, but is expensive and not available in many rural and poorly developed regions. Timely transportation to facilities that stock and administer antivenom may not be available in rural areas with poorly developed emergency medical services. These factors have led to consideration of measures to delay onset of toxicity or alternatives to antivenom therapy. Methods: PubMed searches were conducted for articles on snakebite treatment, or that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…Application of tourniquets is a common first aid practice among snakebite victims in Nigeria and other regions of the world. [ 7 28 31 36 ] The WHO guidelines strongly discourage the use of tourniquets as studies have shown that the use of tourniquet causes tissue anoxia and can trigger severe systemic envenomation after removal and experts recommend slow removal of already applied tourniquet to reduce these effects. [ 15 ] In addition, studies have shown that patients who used tourniquet required higher doses of antivenom and increased hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of tourniquets is a common first aid practice among snakebite victims in Nigeria and other regions of the world. [ 7 28 31 36 ] The WHO guidelines strongly discourage the use of tourniquets as studies have shown that the use of tourniquet causes tissue anoxia and can trigger severe systemic envenomation after removal and experts recommend slow removal of already applied tourniquet to reduce these effects. [ 15 ] In addition, studies have shown that patients who used tourniquet required higher doses of antivenom and increased hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular injections result in fast commencement of systemic toxicity and have poor prognosis even when antivenom is readily available. [ 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…Immobilisation of the bitten part of the body, in a functional position below the level of the heart, reduces lymphatic absorption of the venom. 20 The immobilised child should be transferred to a medical facility as quickly as possible, with the focus on airway and breathing support, prevention of aspiration (of vomitus or other fluids), oxygen administration and gaining intravenous access in an unaffected limb, 20 if available.…”
Section: Management Of Paediatric Snake Envenoming Community Prehospital First Aidmentioning
confidence: 99%
“…Drawbacks of conventional antivenom include adverse allergic reactions, inability to efficiently neutralize all clinical symptoms, and complex production processes that involve animal husbandry and extraction of snake venom. Timely transportation to rural areas is another problem as they usually lack proper medical facilities to stock and administer antivenom [22,23]. In this scenario, medicinal plants could be a viable and less costly option.…”
Section: Introductionmentioning
confidence: 99%